Odontogenic myxoma: A case report of a rare tumor - Andrés Felipe Herrera Ortiz, MD; Bassel Almarie, MD; Natalia Dangon Murcia, MD; Mohammed Amine Farhane, MD (Radiology Case Reports, 2023)
Odontogenic myxoma is a rare and aggressive tumor. Identifying the tumor based on imaging characteristics can pose a challenge due to similarities in features with other tumors, such as ameloblastomas and aneurysmal bone cysts. We report a 33-year-old female who presented with a palpable, tender mass in the lower right jaw. A computed tomography scan revealed a multicystic tumor which was proved to be an odontogenic myxoma. The patient underwent partial surgical resection followed by CO2 laser-assisted evaporation. During 1-year follow-up, the patient showed satisfactory results and no signs of tumor growth. This case report highlights the diagnostic challenges associated with odontogenic myxoma, emphasizing age as a key diagnostic feature.